Піноутворення в технологічних операціях шляхом збивання - Фучаджи, Наталя Олександрівна; Кузьмінська, І. М.; Fuchadzhy, Natalia; Kuzminska, I. (Запоріжжя : 2024, 2024)
UA: Робота присвячена теоретичним дослідженням піноутворення в технологічних операціях харчової промисловості серед збитої продукції. Формування пінної структури в харчовій промисловості в технологічних операціях методом збивання можливо за наявності поверхнево-активних речовин, піноутворювачів, стабілізаторів, роль яких в традиційних технологіях виконують яєчні та молочні продукти або харчові добавки, деякі з яких є частиною рослинної тканини. В харчовій промисловості значну кількість продукції виготовляють шляхом збивання з подальшим отриманням піноподібної структури, яка відіграє важливу роль, оскільки значна група харчових продуктів має пінну структуру. Тому актуальним є розробка наукових принципів регулювання фізико-хімічних та функціональних властивостей пін з метою їх реалізації при виробництві харчової продукції з піноподібною структурою шляхом збивання. EN: The work is devoted to theoretical studies of foam formation in technological operations of the food industry among whipped products. Formation of the structure of this product is possible in the presence of surface-active substances, the role of which in traditional technologies is performed by egg and dairy products or food additives, some of which are part of plant tissue. Today, in the production of whipped products, additives of protein and polysaccharide origin are mainly used, which has caused their extensive study. A large number of products are prepared based on the process of obtaining a foam-like structure, in which the bulk of the volume of the product is occupied by air bubbles. Foams belong to unstable polydisperse systems and have their own technological features. Therefore, foams should be considered as a complex multilayer structure in the form of layers with different thicknesses. Foaming properties of proteins are characterized by foaming ability and foam stability. The first indicator is measured by the volume of foam related to the mass of the protein, the second by its half-life, that is, the time required for the destruction of half of the foam volume. Both indicators depend on the pH of the environment, the concentration of protein, salts, temperature, the presence of lipids, sucrose, dietary fibers, the fractional composition and structure of proteins. The stability of the foam structure is an important factor in improving the quality of food products. The main technological disadvantage and the main problem of using foams is their instability over time and under the influence of external factors, in particular temperature. The solution to these problems is to choose and use a stabilizer that will solve the problem of obtaining a stable foam structure. Foaming processes in the food industry play an important role, since a significant group of food products has a foam structure. Therefore, the development of scientific principles for regulating the physico-chemical and functional properties of foams with the aim of their implementation in the production of food products with a foam-like structure by whipping is relevant.
Foam formation in technological operations through whipping
Keywords: збита продукція; збивання; піноутворення; піна; харчова промисловість; технологічна операція; whipped products; whipping; foaming; foam; food industry; technological operation